SOME OPINIONS ABOUT THE PERSON SHAROF RASHIDOV - Sulaymanova Shohsanam Absamatovna (Western European Studies, 2024)
This article is a political speech about the statesman, writer, diplomat and leading historical figure Sharof Rashidov. Politicians, who from the very beginning correctly noted the laws of social development, develop ideas that are a program for entire nations and states, and carry out major reforms in the country.
Keywords: Political leader; diplomat and public figure; political